A TBET-based ratiometric probe for Au3+ and its application in living cells. Issue 3 (14th December 2015) - Han, Xiang; Zhao, Lei; Wang, Dong-En; Xu, Juan; Zhang, Longlong; Yuan, Mao-Sen; Tu, Qin; Wang, Jinyi
Abstract : A fluorescent probe, RH-Au, based on through-bond energy transfer was developed for the colorimetric and fluorescent detection of Au 3+ . Abstract : In this paper, we designed and synthesized a novel TBET-based ratiometric fluorescent chemodosimeter, RH-Au, for Au 3+ . It was found that the probeRH-Au displayed highly selective, sensitive and naked-eye detection upon the addition of Au 3+ . The probeRH-Au can be used in the pH range 6.0–7.5 and the detection limit was determined to be as low as 2.91 nM (0.57 ppb). We also demonstrated a successful application of imaging Au 3+ in living cells usingRH-Au .